(untitled) - Roy, James A Le (Manila, 1968)
Yestersays in the Philippines including the portrait on the frontispiece: a pleasant, probably arrogant, young Bostonian on the froto-sahid
Keywords: Philippines,Philippine; History,Lịch sử